Order and compromise : government practices in Turkey from the late Ottoman Empire to the early 21st century - Aymes, Marc.; Gourisse, Benjamin.; Massicard, Élise. (Social, Economic and Political Studies of the Middle East and Asia, 2015)
Order and Compromise questions the historicity of government practices in Turkey from the late Ottoman Empire up to the present day. It explores how institutions at work are being framed by constant interactions with non-institutional characters from various social realms. This volume thus approaches the state-society continuum as a complex and shifting system of positions. Inasmuch as they order and ordain, state authorities leave room for compromise, something which has hitherto been little studied in concrete terms. By combining in-depth case studies with an interdisciplinary conceptual framework, this collection helps apprehend the morphology and dynamics of public action and state-society relations in Turkey. Contributors are: Marc Aymes, Olivier Bouquet, Nicolas Camelio, Nathalie Clayer, Anouck Gabriela Corte-Real Pinto, Berna Ekal, Benoît Fliche, Muriel Girard, Benjamin Gourisse, Sümbül Kaya, Noémi Lévy Aksu, Élise Massicard, Jean-François Pérouse, Clémence Scalbert Yücel, Emmanuel Szurek and Claire Visier.